Transformation of Doctors' Work Culture in Supporting Improvement of Service Quality at RSPAU dr. S. Hardjolukito - Diah Ika Hastari; A. Rohendi; Rian Andriani (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Human resources play a vital role in determining the existence and sustainability of an institution, including hospitals as complete health care facilities. The existence of doctors as the main asset demands a continuous transformation of work culture to maintain competitive service quality. This study discusses the transformation of doctors' work culture in supporting the improvement of service quality at RSPAU dr. S. Hardjolukito. The method used is descriptive qualitative with secondary data collection techniques, observation, and interviews. The results of the study show that doctors' work culture is influenced by regulations, SOPs, and internal and external factors, with quite good results (score 4). However, there are challenges in the form of information technology disruption, high workload, and competition between health facilities (score 3). Hospital management responded by clarifying procedures and providing appreciation to improve performance, career, and service quality (score 4).